FAKTA PRAKTIK ILMU HITAM DI FLORES DAN DAYA ILAHI AIR BERKAT - Alexander Jebadu (Jurnal Ledalero, 2019)
Abstract: This article aims to present that sorcery and witchcraftis still widely practiced in Flores. It is one of the main thornysources of social conflicts in almost every village. There havebeen a hot-witch hunts at many regions of the islands. Numerouswitches or sorcerers caught red-handed practicing it were triedaccording customary laws of the villagers and then killed publicly.This article also presents that a number of paranormals can provethe existence of the sorcery practices. The mediums used by theperpetrators can be detected. These mediums were claimed toemit a kind of toxic gas which is thought to cause the victim toget sick and die. This poisonous gas will, however, disappear onlyif it is sprinckled by the sacramental holy water and its victim willslowely recover.Keywords: black magic, sorcery, witchcraft, paranormal, divinepower, holy water.